(3VjGA GdMdhe GdeNJUQ ef TeS GdYdhes - (3eMeO Hf fThGf Hf SYjO Hf fThGf GdMejQi Gdjefi , J (B610 (3g` s; (3fThGf GdMejQj , fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3cJGH GdOGd (B: (3GdOGd heG HYOgG ef GdMQha ai GdeVGYa , HGH GdCSeGA aYd HaJM GdaGA s
(3BNQgG (B:s
(3HGH GdTjf hGdgeRI heG HYOgG hBNQ eG ajgG (B: (3JTGAe GdQLd (B: (3EPG CNP fMh GdTGe hJTGAi eG HjfgeG (B: (3Ci JHGYO Je GdLRA GdKGfi ef cJGH VjGA GdMdhe s
(3GdeNWhWI eQHYI GdTcds
(3fSNI NGeSI cJHJ HNW ajg HYV GdVHWs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GddZIs